EFFECTS OF SALINITY ON OXYGEN CONSUMPTION AND BLOOD PROPERTIES OF YOUNG GREY MULLETS Mugil cephalus - Vitas Atmadi Prakoso; Ki Tae Kim; Byung Hwa Min; Rudhy Gustiano; Young Jin Chang (Center for Fisheries Research, Agency for Marine and Fisheries Research and Human Resource, 2015)
Oxygen consumption (OC) is one of important factors in aquaculture activities, as the oxygen is a vital condition for all the organisms living in the water and having an aerobic type of respiration. OC is the preferred method for measuring and reporting the metabolic rate in fish. The aims of this study were to evaluate the effects of salinity on OC and blood properties of grey mullets. Five experimental groups were conducted to measure OC and blood properties of grey mullets Mugil cephalus (BW: 187.9 ± 45.8 g) according to salinity (30→0 psu, 0→30 psu) changes; SDS: fish reared in seawater (SW, 30 psu) directly shifted to SW, SGF: SW fish gradually shifted to freshwater (FW, 0 psu), SDF: SW fish directly shifted to FW, FDF: FW fish directly shifted to FW, and FDS: FW fish directly shifted to SW. The result showed that OC tended to decrease in the groups of SW fish shifted to FW showing 194.5 mg O2/kg/h at 25°C in SDS to 82.4 mg O2/kg/h at 15°C in SGF. On the contrary, OC increased in the groups of FW fish shifted to SW showing 80.5 mg O2/kg/h at 15°C in FDF to 184.0 mg O2/kg/h at 25°C in FDS. Cortisol levels at the end of experiments were rapidly increased with the lowering salinities in SW fish shifted to FW showing 20.6 ng/mL in SDS to 316.2 ng/mL in SDF, while those were decreased with the increasing salinities in FW fish shifted to SW showing 40.2 ng/mL in FDF to 10.3 ng/mL in FDS. However, glucose levels showed no significant differences among all experimental groups. Based on the information from this study, aquaculture of grey mullet might be applied or developed in freshwater due to its osmotic adaptation ability.